Local Discontinuous Galerkin Methods with Decoupled Implicit-Explicit Time Marching for the Growth-Mediated Autochemotactic Pattern Formation Model (Advances in Applied Mathematics and Mechanics, 2023)
In this paper, two fully-discrete local discontinuous Galerkin (LDG) methods are applied to the growth-mediated autochemotactic pattern formation modelin self-propelling bacteria. The numerical methods are linear and decoupled, whichgreatly improve the computational efficiency. In order to resolve the time level mismatch of the discretization process, a special time marching method with high-orderaccuracy is constructed. Under the condition of slight time step constraints, the optimal error estimates of this method are given. Moreover, the theoretical results areverified by numerical experiments. Real simulations show the patterns of spots, rings,stripes as well as inverted spots because of the interplay of chemotactic drift andgrowth rate of the cells.